2012
DOI: 10.1002/pen.23278
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of polyethylene glycol and ammonium polyphosphate on intumescent flame‐retardant polypropylene

Abstract: A novel flame-retardant system of isotactic polypropylene (iPP) is prepared using polyethylene glycol (PEG) and ammonium polyphosphate (APP). The flammability of iPP/PEG/APP composites containing 20 wt% APP improves with the increase of PEG concentration in the range of 3-15 wt%. The limit oxygen index (LOI) of iPP/ PEG/APP composites reaches up to 30% with 15 wt% PEG concentration in the composites. At the same time, the mechanical properties of iPP/PEG/APP composites demonstrate that PEG can enhance toughnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…APP/ polyethylene glycol combination has proved to impart both good flame retardancy and toughness to iPP [223]. Finally, a novel organophosphorus containing spiro and caged bicyclic phosphate was found to have good interactions with both APP [224] and melamine [225].…”
Section: Table 12mentioning
confidence: 96%
“…APP/ polyethylene glycol combination has proved to impart both good flame retardancy and toughness to iPP [223]. Finally, a novel organophosphorus containing spiro and caged bicyclic phosphate was found to have good interactions with both APP [224] and melamine [225].…”
Section: Table 12mentioning
confidence: 96%
“…Since earlier experience and also the conclusions drawn in previous sections indicate that increasing crystallinity and lamella thickness results in decreasing fracture resistance, we must assume that nucleation induces the rearrangement of the phases or some changes in the mobility of amorphous molecules as proposed by some groups 15,20 . We therefore carried out a dynamic mechanical analysis of the samples.…”
Section: Analysis Of Morphology Discussionmentioning
confidence: 91%
“…They observed that the degree of phase separation and crystalline morphology varied considerably as a result, which led to changing hardness and predictably also modified impact resistance. Other groups prepared blends from PP and poly(ethylene glycol) (PEG) and studied the effect of processing conditions 19 as well as annealing 20 on structure and properties. Annealing was shown to change phase structure in PP/PEG blends resulting in a large increase in toughness.…”
Section: Introductionmentioning
confidence: 99%
“…The LDPE degrades in the way of random chain scission, and some hydroxyl groups are generated on the backbone after dehydrogenating and oxidizing of LDPE . Besides, when the temperature increases, AHP first releases phosphine, and then part of phosphine is quickly oxidized into phosphoric acid.…”
Section: Resultsmentioning
confidence: 99%